2011
DOI: 10.1128/cvi.00493-10
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Levels of CCL17 Correlate with Increased Peripheral Blood Platelet Count in Patients with Active Tuberculosis in China

Abstract: Active tuberculosis (TB) has been associated with imbalance of Th1 and Th2 cytokine pattern. Activation of Th1 lymphocytes, gamma interferon (IFN-␥) production and macrophage activation are crucial in defense against mycobacteria, while Th2 activation and interleukin-4 (IL-4) production are associated with TB progressing and with poor clinical outcome after treatment (6).After being secreted, IFN-␥ and IL-4 are rapidly bound by their receptors and/or inactivated by proteases, which leads to difficulty in detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 26 publications
2
19
2
1
Order By: Relevance
“…Similarly, Baynes et al [25] found the MPV to be low in patients with active PTB and suggested that although thrombopoiesis increased in patients with TB, the platelets’ lifetime may have been shortened. Platelets and their indices in active PTB have been addressed in several previous studies [6,26,27,32]. Contrary to our study, Tozkoparan et al [6] found that the MPV was significantly higher in patients with active TB than in control patients with inactive TB and non-specific pneumonia and decreased with anti-TB treatment.…”
Section: Discussioncontrasting
confidence: 92%
“…Similarly, Baynes et al [25] found the MPV to be low in patients with active PTB and suggested that although thrombopoiesis increased in patients with TB, the platelets’ lifetime may have been shortened. Platelets and their indices in active PTB have been addressed in several previous studies [6,26,27,32]. Contrary to our study, Tozkoparan et al [6] found that the MPV was significantly higher in patients with active TB than in control patients with inactive TB and non-specific pneumonia and decreased with anti-TB treatment.…”
Section: Discussioncontrasting
confidence: 92%
“…TH1 is essential for the attack against intracellular mycobacterium tuberculosis while TH2 has been associated with a poor clinical outcome [20] Cytokine CCL7 is released by platelets causing an increase in TH-2 activity as illustrated by Feng et al [22]. Platelet count may therefore have prognostic value in the long term and further research needs to be implemented.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of Mtb infection, T REG are increased in the peripheral blood of TB patients and inhibit production of IFNγ by Mtb-specific CD4 + T cells (393, 394) and CCR4 antagonists promote proliferation of T cells during MVA85A vaccination (395). The ligand for CCR4, CCL17 but not CCL22 has also been shown to be elevated in the serum of active TB patients (396). These data suggest that CCR4 mediated regulation of T cell responses to Mtb antigens may occur during TB and that antagonism of CCR4 maybe a target for therapeutic use or as an adjuvant during vaccination.…”
Section: The Chemokinesmentioning
confidence: 99%